Experimental and simulation study on the deformation behavior, mechanical properties and microstructure of Ti–6Al–4V alloy wires fabricated by hot drawing - Zhijie Gao; Yaozong Mao; Zhiqiang Zhang; Chunguang Bai; Li Zhou (Journal of Materials Research and Technology)
In this study, a combined experimental and simulation method was proposed to determine the friction coefficient involved in wire drawing processes. Subsequently, the hot drawing experiments and finite element analysis (FEA) of Ti–6Al–4V alloy wire were conducted. The influence of drawing parameters, such as drawing temperature (650 °C, 700 °C, 750 °C), speed (1 m/min, 3 m/min, 5 m/min) and deformation (12.9%, 13.7%, 14.8%) on temperature rise, equivalent plastic strain and residual stress were predicted. The temperature rise exhibits a notable decline with the elevation of the initial temperature, the acceleration of the drawing speed, or the reduction of the deformation amount. Additionally, the equivalent plastic strain increases with increasing initial temperature, speed and deformation. The residual compressive stress in the core decreases from −476 MPa to −279 MPa as the initial temperature increases, increases from −312 MPa to −403 MPa with the acceleration of drawing speed, and decreases from −357 MPa to −290 MPa with the reduction of deformation. Furthermore, the experimental results demonstrated that as the initial temperature increased and the drawing speed increased, the tensile strength decreased by 5.09% and 5.31%, respectively. In contrast, as deformation increased, the tensile strength increased by 5.13%. Meanwhile, the relationship between drawing force and tensile strength was corrected. The obtained equation can accurately predict the drawing force of Ti–6Al–4V alloy.